2019
DOI: 10.3390/nu11081783
|View full text |Cite
|
Sign up to set email alerts
|

Dietary and Supplement-Based Complementary and Alternative Medicine Use in Pediatric Autism Spectrum Disorder

Abstract: Previous literature has shown that complementary and alternative medicine (CAM) is steadily increasing in autism spectrum disorder (ASD). However, little data is currently available regarding its use, safety, and efficacy in children with ASD. Thus, the purpose of this study is to describe the use of supplement-based CAM therapies in children between the ages of 4 to 17 years with ASD. This population-based, cross-sectional study evaluated children with ASD regarding supplement use. A total of 210 participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
31
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 26 publications
1
31
0
2
Order By: Relevance
“…We have not found a correlation between GI problems and diets, thus it does not seem that GI problems were a significant cause for putting the child on a diet. Evidence shows that in a sizeable proportion of individuals with ASD, the dietary intervention is a form of complementary and alternative medicine, i.e., practices and products that are not part of conventional Western medical care [ 51 ]. Implementation of a GFCF (gluten-free/casein-free) diet is the most used dietary intervention in ASD [ 23 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We have not found a correlation between GI problems and diets, thus it does not seem that GI problems were a significant cause for putting the child on a diet. Evidence shows that in a sizeable proportion of individuals with ASD, the dietary intervention is a form of complementary and alternative medicine, i.e., practices and products that are not part of conventional Western medical care [ 51 ]. Implementation of a GFCF (gluten-free/casein-free) diet is the most used dietary intervention in ASD [ 23 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Generally, an increasing trend in food supplement use among children and adolescents has been observed [ 57 ], that are given mainly to prevent or treat illnesses [ 58 ]. A study that involved children with ASD reported that the top reasons of parents for giving supplements were also to enhance the child’s diet, and to promote immune system function [ 51 ]. Evidence shows that the most frequently used forms of supplements are vitamins and minerals in a variety of combinations; also in the ASD population [ 47 , 51 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have invited international experts, researchers and authors to submit original research and review articles that address the progress and our current understanding of nutraceuticals/supplements from in vitro and in vivo studies, as well as from clinical trials describing the benefits/adverse effects with underlying mechanisms. This Special Issue presents a compendium of excellent laboratory and clinical studies using plant extracts [ 15 , 16 , 17 , 18 , 19 , 20 ], purified compounds [ 21 , 22 , 23 ], modified formulations [ 22 , 24 ], and probiotics [ 25 , 26 , 27 , 28 ] to improve many health conditions, including metabolic disorders [ 17 , 20 ], cardiovascular disease [ 29 ], muscle metabolism [ 18 , 25 ], obesity [ 16 , 17 , 20 ], neurological disorders [ 30 ], infectious diseases [ 26 , 27 ], aging [ 23 ], and cancers [ 18 , 21 , 24 , 31 ].…”
mentioning
confidence: 99%